THE MEDIATING EFFECT OF HEALTHCARE PROFESSIONAL ENGAGEMENT IN THE RELATIONSHIP BETWEEN TALENT MANAGEMENT, LEADERSHIP AND OMAN GOVERNMENT HOSPITAL PERFORMANCE - Nor Azilah Husin; Khalood Farzah (International Journal of Accounting, Finance and Business, 2023)
This research investigates the role of talent management and healthcare professional engagement in enhancing hospital performance and ensuring sustainability in Oman's healthcare setting. In addition, the need for more research on talent management and retention in healthcare settings highlights the importance of this study, which focuses on healthcare professionals' engagement as a mediator between talent management and hospital performance. The research aims to fill the gap in the literature by analyzing the relationship between talent management, leadership, and hospital performance in Omani public hospitals. The study aims to comprehensively understand the factors affecting healthcare professionals' engagement and its impact on the performance of Omani government hospitals. A cross-sectional study was conducted among healthcare professionals in 11 regions of Oman's government hospitals. The questionnaire was collected from 400 respondents and used the random sampling technique. Smart PLS software was used for structural equation modeling to analyze the collected data. The study emphasizes the importance of talent management and HPE for enhancing hospital performance and ensuring sustainability. The study's measurement scale was reliable and valid, making it helpful in evaluating talent management practices in Omani hospitals. The study's structural model provides a pragmatic framework for understanding the relationship between talent management, HPE, and hospital performance. In addition, this research establishes the significance of the resource-based view theory in discovering the relationship between talent management and healthcare professional engagement and hospital performance via a single model. It contributes to the existing literature by testing the proposed model about leadership, innovation, and healthcare professional engagement. The study also addresses the gaps in the research related to the link between performance and leadership. The research adds to the growing talent management research in hospitals, especially in Oman, and shows that talent management influences hospital performance.